Evidence in the Networked Governance of Regional Decarbonisation: A Critical Appraisal. Issue 2 (20th March 2017) - Weller, Sally; Tierney, John
Abstract: This paper examines the use of evidence in collaborative policy making focusing on the challenges of implementing national decarbonisation policies in regional areas. Its case study of a staged policy intervention to promote the 'transition to a low carbon economy' in Victoria's coal‐dependent Latrobe Valley reveals the selective use of evidence to support policy directions that emerged from the interaction of policy knowledge and the political mood. The paper shows how local conditions can be manipulated to enable the production of evidence consistent with the policy objective, but also suggests that despite combining orchestrated evidence with customised forms of networked governance, it is not possible to suppress or deflect unresolved political disagreements. Abstract : This paper examines the use of evidence in networked governance. Using a staged policy framework, it shows that each stage of the process invoked a different type of evidence. The addition of new evidence shifted the definition of the problem in a way that enabled the process to move to the next stage. The conclusions reflect on the implications of policy‐led evidence for democratic government and the challenges of decarbonisation.